2010
DOI: 10.5194/acp-10-10753-2010
|View full text |Cite
|
Sign up to set email alerts
|

Air mass origins influencing TTL chemical composition over West Africa during 2006 summer monsoon

Abstract: Abstract. Trace gas and aerosol data collected in the tropical tropopause layer (TTL) between 12-18.5 km by the M55 Geophysica aircraft as part of the SCOUT-AMMA campaign over West Africa during the summer monsoon in August 2006 have been analysed in terms of their air mass origins. Analysis of domain filling back trajectories arriving over West Africa, and in the specific region of the flights, showed that the M55 flights were generally representative of air masses arriving over West Africa during the first 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
60
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(70 citation statements)
references
References 52 publications
10
60
0
Order By: Relevance
“…Fierli (unpublished) and Khaykin et al (2009), do show evidence for overshooting over West Africa. As a result evaporation of the ice particles lead to hydration within the TTL and lower tropical stratosphere (Corti et al, 2008) during TROCCINOX and SCOUT-O3.This is in reasonable agreement with the analysis of Law et al (2010), although they found an influence from lower stratospheric air in the mid and upper TTL during the SCOUT-AMMA campaign period.…”
Section: Atmospheric Background In 2005 and 2006supporting
confidence: 80%
See 2 more Smart Citations
“…Fierli (unpublished) and Khaykin et al (2009), do show evidence for overshooting over West Africa. As a result evaporation of the ice particles lead to hydration within the TTL and lower tropical stratosphere (Corti et al, 2008) during TROCCINOX and SCOUT-O3.This is in reasonable agreement with the analysis of Law et al (2010), although they found an influence from lower stratospheric air in the mid and upper TTL during the SCOUT-AMMA campaign period.…”
Section: Atmospheric Background In 2005 and 2006supporting
confidence: 80%
“…While N 2 O has a long lifetime, is well mixed within the troposphere, and has only one sink in the stratosphere, the ozone abundance is influenced by tropospheric photochemical sources and is not well suited as dynamical tracer in particular in the tropics. As Law et al (2010) demonstrate, this might lead to differences in lower TTL gradients because the ozone concentrations in the TTL vary significantly in dependency of location and season. For these reasons it is not surprising that the data from the campaigns are on different "branches" of the correlations shown in the right panel of Fig.…”
Section: Vertical Profiles Of Submicron Particle Mixing Ratios In Thementioning
confidence: 99%
See 1 more Smart Citation
“…trajectories based on large-scale wind fields alone underestimate rapid vertical transport in the tropics. For example, Law et al (2010) have suggested that use of such trajectories underestimates the contribution of deep convection over Asia to the air masses in the tropical tropopause layer (TTL) observed over west Africa and estimates of convective transport based on trajectories calculated explicitly in a mesoscale model appear to show deeper transport of air masses into the tropical tropopause layer . The inclusion of the convective parameterization in the FLEX-PART trajectory code clearly has a significant impact on our results and may go some way to improving the representation of transport based on large-scale trajectories alone.…”
Section: Methodsmentioning
confidence: 99%
“…• 3D box surrounding the flight path, analogously to Law et al (2010). The closest starting point (in space, time, and height) is attributed to each point of the flight path.…”
Section: Temperature Humidity and Ozonementioning
confidence: 99%